Percepção de pais sobre o período da adolescência e transição para a vida adulta de seus filhos com paralisia cerebral - Ana Paula Machado Silvério (2020)
Parents of individuals with CP are the primary caregivers and providers of support for their children. During adolescence, caregivers play a key role in health care and involving their children in daily activities. In recent years, there has been an increase in the body of knowledge in relation to transition services with actions directed at adolescents with CP, since they have difficulties during this phase of life. However, these studies report the importance of services that address the specific needs of parents, in order to assist them in the challenges experienced during adolescence and the transition to adulthood of their children with CP. This study aimed to understand how parents of adolescents with CP experience adolescence and the transition to adulthood for their children and to identify characteristics for developing a support service for parents of adolescents with CP. A qualitative study was conducted with 19 families of adolescents with CP of both sexes, among 12 and 18. Parents were recruited from the Associação Mineira de Reabilitação. At first, individual interviews with parents were conducted using a semi-structured script. After the interviews, parents were invited to participate in focus groups. The content of the interviews and focus groups were recorded and transcribed for content analysis. Three categories emerged: (1) “The arrival of adolescence” (2) “What will be the future?” (3) “Support and services: Paths to follow”. The results suggest that adolescence can be a challenging phase for parents of adolescents with CP, since the behavior changes already expected by adolescence seem to be intensified by the low participation of adolescents in social activities and comparison with normal development peers. Parents projected their desire for their children to become independent in the future. Regarding their future, they aimed to return the occupational roles that were interrupted with the child's arrival. Information from the present study guided the design of a program for parents of adolescents with CP in the transition to adulthood, considering the format, content, and outcomes to be achieved.